1999
DOI: 10.1142/s0960313199000088
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Study of Manifold Microchannel Heat Sinks for Electronic Cooling Design

Abstract: Advances in microfabrication technology have allowed the use of microchannels in ultra compact, very efficient heat exchangers, which capitalize on the channels large surface area to volume ratio to transport high heat fluxes with small thermal resistances. One example is the cooling of microchips. However, the research into microscale flow and heat transfer phenomena conducted by various researchers provided substantial experimental data and considerable evidence that the behaviour of fluid flow and heat tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Second, the secondary local maxima starts to appear close to the impingement zones under the inlet and outlet feed channels. Similar local high heat transfer zones were reported by Copeland (1995), Copeland et al (1997) and Ng and Poh (1999). Close to the impingement zones, the local fluid acceleration and vortices created during the flow turning have the effect of reducing the thermal Finally, the surface temperature distributions on the fin surface, microchannel base, and middle of the base material are shown in Fig.…”
Section: Numerical Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Second, the secondary local maxima starts to appear close to the impingement zones under the inlet and outlet feed channels. Similar local high heat transfer zones were reported by Copeland (1995), Copeland et al (1997) and Ng and Poh (1999). Close to the impingement zones, the local fluid acceleration and vortices created during the flow turning have the effect of reducing the thermal Finally, the surface temperature distributions on the fin surface, microchannel base, and middle of the base material are shown in Fig.…”
Section: Numerical Resultssupporting
confidence: 84%
“…The geometrical design that delivered the lowest thermal resistance was compared with a traditional microchannel heat sink, and it was found that the FFMHX design would work with 35 % less thermal resistance at the same pumping power. Ng and Poh (1999) analyzed thermal performance of FFMHXs numerically for 16 cases with different geometrical dimensions and flow conditions. The numerical model was validated by the experimental results of Copeland (1995).…”
Section: Survey Of State Of the Art Research In The Fieldmentioning
confidence: 99%
“…Manifold microchannel heat sinks were first suggested in Harpole and Eninger [8] and numerically studied by Copeland et al [9] and Ng and Poh [10]. Compared to conventional microchannel heat sinks, manifold microchannel heat sinks feature many inlet and outlet manifolds, alternating at a periodic distance along the length of the microchannels.…”
Section: Motivationmentioning
confidence: 99%
“…Among variable geometric parameters affecting the performance of microchannels, the channel width and height are crucial factors 21‐23 . Since the geometry of the channel cross‐section is collectively determined by both width and height, a dimensionless parameter, aspect ratio (italicAR=HC/WC) has been introduced to investigate the effects of microchannel geometry on flow and heat transfer performance.…”
Section: The Geometric Parameters Of Channelmentioning
confidence: 99%